Los algoritmos de reconocimiento facial y su uso en la potenciación de la seguridad de los estudiantes de la Universidad Técnica De Babahoyo - Bajaña Ortiz, Octavio Alexander (2023)
The objective of this research is to enhance the security of the students of the Technical University of Babahoyo through the analysis of facial recognition algorithms. To achieve this objective, a study will be conducted to identify the most appropriate places for the implementation of the facial recognition system and the most suitable algorithms will be selected. In addition, the technical requirements necessary to implement the system will be determined. Similarly, the possibility of integrating this system with other security tools should be explored and its impact on the perception and reputation of the university in the field of technology and security should be explored. In short, this project aims to provide an efficient and modern solution to improve the security of the student community at the Technical University of Babahoyo.